Rethinking Practice as Research and the Cognitive Turn - May, S. author. aut Link
VIII, 84 p.
Keywords: The last 15 years has seen an explosion of studies that use cognitive science to understand theatre, whilst at the same time theatre-makers are using their artistic practice to address research question. This book looks at the current discourse around these emerging fields.